Advertisement Remove all ads

Factorise (L + M)Square2 − (L − M)Square2 - Mathematics

Factorise (l + m)2 − (l − m)2

Advertisement Remove all ads

Solution

(l + m)2 − (l − m)2 = [(l + m) − (l − m)] [(l + m) + (l − m)]

[Using identity a2 − b2 = (a − b) (a + b)]

= (l + m − l + m) (l + m + l − m)

= 2× 2l

= 4ml

= 4lm

Concept: Factorisation Using Identities
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 8 Maths Textbook
Chapter 14 Factorisation
Exercise 14.2 | Q 2.5 | Page 223
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×